Stronger together - democracy and gender equality in Europe - Lux, Julia (My University, 2024)
What's gender equality got to do with democracy? Why is an intersectional understanding of gender equality more democratic? And what's happening in the European Union to foster gender equality and democracy? The Dossier engages with these questions in depth: The topic is introduced by Julia Lux (Observatory). In his statement, Robert Biedroń (Chair of the FEMM-Committee in the European Parliament) recapitulates the EU parliamentary equality policy efforts during the legislative period 2019–2024. Belinda Dear (ILGA-Europe) and Julie Pascoët (ENAR) highlight in the interview where reform is needed from an intersectional perspective on equality. Gabriele Abels (University of Tübingen, Germany) discusses the Commission initiative Union of Equality. To top it off, theses on the relationship between democracy and gender equality by Julia Lux (Observatory) provide food for thought.
Keywords: Democracy; Intersectionality; European Union; 320 Politikwissenschaft; Gender Equality; Union of Equality